On gauge invariance and ward identities for the Wilsonian renormalisation group - Litim, Daniel F.; Pawlowski, Jan M. (Nuclear physics. Proceedings supplements, 1999)
We investigate non-Abelian gauge theories within a Wilsonian Renormalisation Group approach. The cut-off term inherent in this approach leads to a modified Ward identity (mWI). It is shown that this mWI is compatible with the flow and that the full effective action satisfies the usual Ward identity (WI). The universal 1-loop β-function is derived within this approach and the extension to the 2-loop level is briefly outlined.
Gesehen am 07.12.2017